Electrochemical synthesis and characterization of BaB6 from molten melt - Jose T.P.; Sundar L.; Berchmans L.J.; Visuvasam A.; Angappan S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Barium hexaboride (BaB6) crystals were electrochemically synthesized using molten salt technique. Barium carbonate (BaCO3) and boron trioxide (B2O3) was used as reactants. Lithium fluoride (LiF) was used as the supporting electrolyte. The molten electrolyte consisted of 50 wt % BaCO3 and B2O3 with different stiochiometric ratios of Ba and B and 50 wt % lithium fluoride. DTA/TGA studies were made to determine the eutectic point of the melt and it was found to be around 821oC. The electrolytic cell had a high purity graphite crucible, which served as the electrolyte holding vessel and also as the anode for the electrolysis. An electro-polished molybdenum rod was employed as the cathode. The electrolysis was performed at 870ºC under argon atmosphere, at current densities ranging from 0.2-0.5 A/cm2. The electrodeposited crystals were examined for the phase identification using X-ray diffraction technique. The AAS and the chemical analysis were made for the determination of chemical composition of the synthesized crystals. The purity of the crystals was also assessed using ICP-MS, XRF and EDX, which reveal that the crystals were associated with trace amount of impurities like oxygen, carbon and iron. The compound is found to be more than 99 % pure. The morphology of the crystals was examined using Scanning Electron Microscopy (SEM). From the above studies, it is concluded that the molten salt process is a simple preparative procedure for the synthesis of sub-micron size barium hexaboride crystals.